2008
DOI: 10.1128/jvi.01001-08
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Spectrum of Genomic Integration of Recombinant Adeno-Associated Virus Serotype 8 Vector in Neonatal Mouse Liver

Abstract: Neonatal injection of recombinant adeno-associated virus serotype 8 (rAAV8) vectors results in widespread transduction in multiple organs and therefore holds promise in neonatal gene therapy. On the other hand, insertional mutagenesis causing liver cancer has been implicated in rAAV-mediated neonatal gene transfer. Here, to better understand rAAV integration in neonatal livers, we investigated the frequency and spectrum of genomic integration of rAAV8 vectors in the liver following intraperitoneal injection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 46 publications
0
39
0
Order By: Relevance
“…The rapid decline of ALP activity after AAV injection is thought to be due to a reduction of ALP expression in the liver. It was reported that AAV vector transduces the neonatal liver with high efficiency, but the expression is rapidly decreased mainly because episomal vector genomes are degraded in the liver at this developmental stage (Cunningham et al, 2008;Inagaki et al, 2008). There was no significant difference in bone mineralization between lentiviral-and AAV-treated mice.…”
mentioning
confidence: 76%
“…The rapid decline of ALP activity after AAV injection is thought to be due to a reduction of ALP expression in the liver. It was reported that AAV vector transduces the neonatal liver with high efficiency, but the expression is rapidly decreased mainly because episomal vector genomes are degraded in the liver at this developmental stage (Cunningham et al, 2008;Inagaki et al, 2008). There was no significant difference in bone mineralization between lentiviral-and AAV-treated mice.…”
mentioning
confidence: 76%
“…It was reported that serotype 8 AAV (AAV8) or AAV9 vector efficiently transduced both neonatal and adult liver, but the gene expression is only transient in neonatal liver. 17 The rapid decline of gene expression in the neonatal liver could be due to dilution and degradation of episomal vector genomes during active cell mitosis. Post-mitotic tissues such as the muscle, heart and brain are important targets for AAVmediated neonatal gene therapy for long-term expression.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of both the positive and the negative strand in the rAAV vector to overcome this reduces the coding capacity by a factor of two and, thus, potentially limits the possible genes of interest even further [24]. Lastly, rAAV-induced tumorigenesis has been suggested when high incidences of hepatocellular carcinomas were found in one particular clinical trial [25], possibly resulting from the rAAV preference of integration near active genes; however, evidence is still very limited and unconfirmed by other studies [26]. In addition, correct gene targeting may become positively influenced by the depletion Ku70 -one half of a heterodimeric protein complex involved in the initial steps of homologous recombination, thereby, (partially) counter acting harmful side effects of rAAV vector systems [27], whereas the small coding capacity would not pose a problem for the delivery of constructs encoding miRNAs to frustrate the current replication of viruses without attenuated vaccine or modify the expression of miRNA-responsive genes [28,29].…”
Section: Future Science Groupmentioning
confidence: 92%